The Influence Of Training And Career Development On Employee Performance In PT. Temprint West Jakarta - Shela Indah Savitri; Camelia Putri Iskandar (SEAN Institute, 2024)
This research was conducted because there were problems related to the lack of training and career development which were thought to affect employee performance at PT. Temprint West Jakarta. This research aims to examine the effect of training and career development on employee performance at PT. Tempprint West Jakarta. The population in this study were all employees of PT. Tempprint West Jakarta and the research sample was 80 employees. Data analysis using simple, multiple linear regression, classical assumption testing, hypothesis testing and coefficient of determination. The results of this research show that simultaneously the training and career development variables have a significant effect on employee performance. The significant positive influence on the variables training (X1) and career development (X2) has a positive and significant influence on employee performance (Y) with a correlation value of 0.835, meaning it has a strong influence. Coefficient of determination 83.5%. Hypothesis testing obtained fcount > ftable or (194.885 > 3.115). The resulting tcount (17.952) > ttable value (1.664) and the p-value is also clearly significant, namely less than the specified significance level (0.000 < 0.05). Thus, Ho is rejected and Ha is accepted, so from this research it can be concluded that there is a positive and significant influence between the variables Training (X1) and Career Development (X2) on employee performance (Y) PT. Tempprint West Jakarta.